STABILIZING THE THERMAL TEMPERATURE OF LITHIUM BATTERIES USING PELTIER PLATE FOR EV VEHICLES - MISS. EKATA S. CHAVAN; MR. MILIND C. BUTALE (International Journal of Innovations in Engineering Research and Technology, 2021)
Lithium batteries have become widwly used in energy storage systems. Since adverse operating temperatures can impact battery performance, degradation, and safety achieving a battery thermal management system that can provide a suitable ambient temperature environment for working batteries is important. This paper provides a review based on previous based on previous studies, summarizes the electrical and thermal characteristics of batteries and how they are affected by the operating temperature, analyzes the relative merits and specific purposes of different cooling or heating methods, and provides many optimization mrthods. Moverover, because low power consumption, a high temperature regulation capacity, and excellent temperature uniformity are desired for every battery thermal management system, we also present control strategies that can contribute to thermal management. It is indispensable to establish criteria to evaluate battery thermal management systems. We subsequently summarize the characteristic parameters for the analysis of various battery thermal management system desig s. Finally, we provide an outlook for the development of lithium-ion battery thermal management systems.